Academic library outreach program encounters / Nur Amira Eliana Abd Halim and Roziya Abu - Abd Halim, Nur Amira Eliana; Abu, Roziya (Universiti Teknologi MARA, Kedah, 2018)
Outreach is often used interchangeably with synonyms such as an extension of service and the phrases, for instance ‘service to the disadvantaged’ or ‘service to the unserved’ and ‘service to the community’ and/or the ‘inner-city service’. What many fails to understand is that the modifications in the goals and the type of library service will describe its outreach approach differently, although the interchangeability of terms and the lack of specificity of their definition still remain. The aim of this article is to discover and deliberate on the factors that affect an outreach program in an academic library. In doing so, study result from two Institutes of Teacher Education (IPG) in the State of Kedah is selected. This study adopts a qualitative case study approach with in-depth individual interviews of the leading librarian for each institution, and later the thematic content analysis and cross-case analysis is used throughout this study in order to analyze the data. From the result of the interviews in the two Institutes of Teacher Education (IPG) in the State of Kedah (namely, CS1 and CS2), two most important factors emerge, and it is said to be the key factor the effect an academic library outreach programs. Those factors are: 1) Financial Factor and 2) Staffing Factor